2021
DOI: 10.2147/cmar.s286205
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA TRIM52-AS1 Promotes Growth and Metastasis via miR-218-5p/ROBO1 in Hepatocellular Carcinoma

Abstract: Background: Hepatocellular carcinoma (HCC) is a malignant disease with a high mortality among primary HCC patients worldwide. Lots of studies have shown that lncRNAs are known as the biomarkers in diagnosis, treatment and prognosis of hepatocellular carcinoma. Therefore, clarifying the detailed function and mechanism of the lncRNA in the HCC progressing seems particularly important. Methods: The TCGA and GEO database and RT-qPCR were used to analyse the expression of TRIM52-AS1 in HCC tissues and cell lines. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Studies on hepatocellular carcinoma (HCC) have shown that the TRIM52-AS1 knockdown inhibits the proliferation and metastasis of HCC cells. TRIM52-AS1 behaves as a competitive endogenous RNA (ceRNA) and promotes the progression of HCC by sponging the miRNAs and up-regulating the expression of the mRNAs that are regulated by miRNAs [ 49 , 50 ]. Therefore, it can be concluded that TRIM52-AS is down-regulated in CC tissues; this attenuates the sponging effect on miR-378a, and increases the binding of miR-378a to GZMB, which in turn inhibits and down-regulates the expression of GZMB.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on hepatocellular carcinoma (HCC) have shown that the TRIM52-AS1 knockdown inhibits the proliferation and metastasis of HCC cells. TRIM52-AS1 behaves as a competitive endogenous RNA (ceRNA) and promotes the progression of HCC by sponging the miRNAs and up-regulating the expression of the mRNAs that are regulated by miRNAs [ 49 , 50 ]. Therefore, it can be concluded that TRIM52-AS is down-regulated in CC tissues; this attenuates the sponging effect on miR-378a, and increases the binding of miR-378a to GZMB, which in turn inhibits and down-regulates the expression of GZMB.…”
Section: Discussionmentioning
confidence: 99%
“…The TRIM52 protein belongs to the C-V isoform of the TRIM protein family, with 1 RING structure at a time from the N-terminal to the C-terminal, a B-Box2 structural domain, and lacking a distinct double helix structural domain and C-terminus. It has been shown as a promoter in ovarian cancer (12), hepatocellular carcinoma (13,15), and renal cancer (14), while its role in the development of CC had not been clarified Our study demonstrated that TRIM52 is significantly highly expressed in CC cell lines. Cell proliferation and cell cycle showed a statistically significant decrease of approximately 20.83% in the proportion of S-phase cells in HCT116 cells following knockdown of TRIM52.…”
Section: Discussionmentioning
confidence: 63%
“…Non-coding (lnc)RNA TRIM52-AS1 knockdown inhibited the proliferation and metastasis of hepatocellular carcinoma cells. It has been shown to promote the growth and metastasis of hepatocellular carcinoma via miR-218-5p/ROBO1 (15). It was reported that TRIM52 upregulation promotes proliferation and invasiveness through activation of the Wnt/β-catenin pathway in lung cancer cells (16).…”
Section: Introductionmentioning
confidence: 99%
“…While little is known about the role of SLIT3 in the placenta, SLIT2 and its receptor, roundabout guidance receptor 1 (ROBO1), have been suggested to regulate trophoblast proliferation and differentiation and their aberrant signaling may be associated with various pregnancy-related disorders ( Li et al, 2015 ; Li et al, 2017 ; Tiensuu et al, 2019 ). Interestingly, ROBO1, which is a functional target of miR-218-5p ( Liu Y. et al, 2021 ), is upregulated in preeclamptic placentas ( Liao et al, 2012 ).…”
Section: Microrna Regulation Of Trophoblast Invasion Spiral Artery Re...mentioning
confidence: 99%